Genetic differential susceptibility to the parent-child relationship quality and the life span development of compassion - Dobewall Henrik; Keltikangas-Järvinen Liisa; Saarinen Aino; Lyytikäinen Leo-Pekka; Zwir Igor; Cloninger Robert; Raitakari Olli T; Lehtimäki Terho; Hintsanen Mirka (WILEY, 2022)
The development of compassion for others might be influenced by the social experiences made during childhood and has a genetic component. No research has yet investigated whether the parent-child relationship quality interacts with genetic variation in the oxytocin and dopamine systems in predicting compassion over the life span. In the prospective Young Finns Study (N = 2099, 43.9% men), we examined the interaction between mother-reported emotional warmth and intolerance toward their child assessed in 1980 (age of participants, 3-18 years) and two established genetic risk scores for oxytocin levels and dopamine signaling activity. Dispositional compassion for others was measured with the Temperament and Character Inventory 1997, 2001, and 2012 (age of participants, 20-50 years). We found a gene-environment interaction (p = .031) that remained marginally significant after adjustment for multiple testing. In line with the differential susceptibility hypothesis, only participants who carry alleles associated with low dopamine signaling activity had higher levels of compassion when growing up with emotionally warm parents, whereas they had lower levels of compassion when their parents were emotionally cold. Children's genetic variability in the dopamine system might result in plasticity to early environmental influences that have a long-lasting effect on the development of compassion. However, our findings need replication.